Atomic diffusion mediated by vacancy defects in pure and transition element (TM)-doped (TM = Ti, Y, Zr or Hf) L12 Al3Sc. (15th October 2016) - Shi, Tao-Tao; Wang, Jia-Ning; Wang, Ya-Ping; Wang, Hai-Chen; Tang, Bi-Yu
Abstract: Atomic diffusion in pure and transition element (TM = Ti, Y, Zr or Hf)-doped Al3 Sc has been studied mainly along vacancy-mediated diffusion paths. After the point defect formation energies are determined, the energy profiles for dominant diffusion paths are obtained using climbing image nudged elastic band method. The energetic results show that Al atom diffusion through nearest-neighbor jump mediated by Al vacancy is most favorable due to the lowest activation barrier, the other diffusion processes would make very small contribution due to the high activation barrier or unstable final state. The dominant Sc atom diffusion mechanisms are the Al-vacancy mediated nearest-neighbor jump under Al-rich condition and antistructure sublattice mechanism under Sc-rich condition. The 6-jump cycle and next nearest-neighbor jump are greatly restricted with high activation barriers. Moreover, effect of typical transition element (Ti, Y, Zr or Hf) doping on atomic diffusion is further studied. The activation barriers for dominant diffusion mechanisms increase with increasing atom size mismatch in sequence of Zr < Hf < Ti < Y dopant. Graphical abstract: Highlights: The point defects formation energies are determined in pure and doped Al3 Sc. The energy profiles for dominating diffusion paths are obtained using climbing image nudged elastic band method. Al atom nearest-neighbor jump mediated Al vacancy is most favorable for Al atom diffusion. Sc mainly diffuses by nearest-neighbor jump and antistructure sublattice mechanisms mediated by Al vacancy. The activation barriers increase with increasing atom size mismatch in transition metal-doped Al3 Sc.